proof- tan2A.sec2(90-A)-sin2A.cosec2(90-A)=1.​

Question

proof- tan2A.sec2(90-A)-sin2A.cosec2(90-A)=1.​

in progress 0
Reagan 1 month 2021-08-17T19:08:48+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-08-17T19:10:43+00:00

    Answer:

    PROVED BELOW 🙂

    Step-by-step explanation:

    i ) sec(90-A) = cosecA

    ii) cosec(90-A) = secA

    Here,

    LHS = tan²Asec²(90-A)-sin²Acosec²(90-A)

    = tan²Acosec²A-sin²Asec²A

    = tan²Acosec²A – sin²A/cos²A

    = tan²Acosec²A – tan²A

    /* sinA/cosA = tanA */

    = tan²A(cosec²A-1)

    /* cosec²A-1 = cot²A */

    = tan²Acot²A

    = 1/cosA

    /*tanAcotA=1*/

    = 1

    = RHS

    PLS MRK AS BRAINLIEST PLSSSSSSSS I HELPED U SO MRK AS BRAINLIEST 🙂

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )